Comparative enantiomer affinity pattern of β‐blockers in aqueous and nonaqueous CE using single‐component anionic cyclodextrins. Issue 11 (29th January 2015) - Feng, Ying; Wang, Tingting; Jiang, Zhengjin; Chankvetadze, Bezhan; Crommen, Jacques
Abstract : A series of eight chiral β‐blocker drugs, acebutolol, atenolol, carazolol, carteolol, carvedilol, propranolol, sotalol, and talinolol, have been enantioseparated using two single‐component anionic β‐CD derivatives, namely heptakis (2, 3‐di‐ O ‐methyl‐6‐sulfo)‐β‐CD (HDMS‐β‐CD) and heptakis (2, 3‐di‐ O ‐acetyl‐6‐sulfo)‐β‐CD (HDAS‐β‐CD), in aqueous CE and NACE. The influence of the nature of substituents (methyl or acetyl) in positions 2 and 3 on the CD derivatives and of the electrophoretic medium (water or methanol) on the enantioselectivity and enantiomer affinity pattern (EAP) of these structurally related compounds was systematically studied. All eight β‐blockers could be enantioseparated at least partially in the four CE systems, except sotalol with HDMS‐β‐CD in NACE. In general, lower affinity and enantioselectivity were obtained in the presence of HDMS‐β‐CD compared to HDAS‐β‐CD. Reversals of EAPs were observed for all compounds. EAPs toward these two CDs were found to be opposite to each other in NACE for all compounds except carvedilol and in aqueous CE for atenolol, carteolol, talinolol, and sotalol. It is particularly noteworthy that opposite EAPs were also observed using the same CD derivative when the aqueous BGE was replaced with the methanolic one: for carazolol, carvedilol, and propranolol in the presence of HDMS‐β‐CD and for acebutolol and carvedilol with HDAS‐β‐CD.